Dendritic cell protocols - Robinson, Stephen P; Stagg, Andrew J (Humana Press, 2001)
Stephen P Robinson, MD, PhD, and Andrew Satgg, PhD, have brought together a wide range of time-proven methods for studying these dendritic cells. Many of these readily reproducible techniques deal with the problem of obtaining sufficient dendritic cells for analysis, whether by isolation from a wide vareity of tissues, or from various progenitor cell populations. Other methods describe in step-by-step fashion the techniques commonly used for analyzing aspects of dendritic cells, ranging from cell migration to antigen uptake and T cell stimulation. In addition, a few techniques explore the practical challenges involved in using dendritic cells in a clinical setting to develop novel immunotherapeueutics.
Methods in molecular medicine ; Vol. 64
Keywords: cytologie, klinická cytologie; Dendritic Cells; dendritické buňky; biologie